The educational-methodological support evolution of library local history courses - L. G. Taranenko (Библиосфера)
Regional library local history is a comprehensive library activity requiring special professional training. The author reveals the issue of teaching library local history at library higher schools; searched educational publications on local history in the electronic catalogues of libraries and bibliographic indices. It was revealed 48 academic publications on library local history for 1930-2014. The study objective is to trace the evolution of educational publications on the problems of teaching librarian local history in a library higher school. It was presented the analysis of textbooks on the following features: types of educational publications, authors, scientific schools and content. The study revealed expanding diversity of educational publications on library local history, from single programs, lectures to textbooks, educational-methodical complexes and electronic textbooks. At the same time, it was found out a lack of new integrated textbooks, «fragmentation» in teaching and representing certain aspects of local librarian history in educational work, insufficient number of electronic textbooks and absence of interactive electronic educational materials for universities. The fundamentals of teaching local librarian history were started by two scientific schools in St. Petersburg State Institute of Culture and Moscow State Institute of Culture. The formation of the library local history as an educational course is associated with the name of N. V. Zdobnov. The largest contribution to the development of educational-methodological support for library local history was made by A. V. Mamontov and N. N. Shcherba. The substantive aspect of educational-methodological support for library local history can be divided into three stages. The first stage (1930-1970) is related to the study of local history bibliography only. The second period (1980-1990) is characterized by creating a number of editions covering general problems of regional studies of library local history and library activities on local history study. In 1990s preconditions appeared to expand study of various aspects of library local history. IIt was connected with changes in the state policy of regional development, as well as a growing interest in regional/local history information. The third stage (2000-2010s) of the evolution of educational publications is related, on the one hand, to a more expanded study of some specific aspects of library local librarian (bibliographic processing of local history documents, local history fund or management of local history activities, etc.), on the other hand, to a complex representation of regional studies in cooperation of libraries, archives, museums and other institutions dealing with issues of local history in the region.